Huanglongbing has reached the Central American region - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Huanglongbing (Diaphorina citri) or greening disease recently reached the Caribbean. This bacterial disease poses a serious threat to citrus crops. It affects the softer parts of citrus trees, like leaves, fruit, and young twigs. Loss of leaves is...